The poor under globalization in Asia, Latin America, and Africa - Nissanke, Machiko; Thorbecke, Erik, 1929-; World Institute for Development Economics Research (Oxford : Oxford University Press, 2010)
This volume uses 13 case studies to analyze the impact of economic globalization on poverty and inequality in different regions of the developing world.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Globalization -- Economic aspects -- Developing countries -- Congresses